To the centenary of the birth of outstanding evolutionist Dmitri Konstantinovich Belyaev - V. K. Shumny (Вавиловский журнал генетики и селекции)
This paper is a tribute to outstanding evolutionary biologist Dmitri Konstantinovich Belyaev in connection with the forthcoming centenary of his birth. His work on variation-related mechanisms in animal domestication made this process much faster. Belyaev is at length described as a person, as a scientist and as the organizer of the Institute of Cytology and Genetics of the Siberian Branch of the USSR Academy of Sciences. The author had for many years worked as Belyaev’s Deputy for Science, and, when Dmitri Konstantinovich passed away, had for 22 years headed the Institute of Cytology and Genetics. Belyaev’s life was not easy: he was a priest’s son and an “enemy of the people”’s brother. He was in the battlefield all through the Great Patriotic War and became a man of steel. His struggle for the restoration of genetics in the country, his commitment to setting up and maintaining relationships between masters and followers and many more other aspects of his life are considered. The global importance of the “master – follower” paradigm as a basis of the continuity of generations is underlined and re-underlined, for this is a very special point in the scientific community, especially when new schools of science emerge.